Konsep Nomokrasi Islam dalam Pemikiran Tahir Azhari - Cinta Nor Azizah; Halisah Halisah; Nor Yelly; Surya Sukti (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This article discusses the concept of Islamic nomocracy in the thought of Tahir Azhary as a concept of the rule of law that places law as the highest authority in the administration of state life. According to his view, Islamic nomocracy is a constitutional system based on sharia principles, emphasizing the supremacy of law, justice, equality, consultation (shura), and the protection of public rights. This concept is closely related to the fundamental elements of fiqh siyasah such as constitution (dustur), legislation (al-sulthah al-tasyri’iyah), democracy, ummah, and shura as normative foundations in Islamic governance. Constitution is understood as the highest legal basis limiting power, while legislation functions to establish rules based on the Qur'an and Sunnah. Democracy in Islam is reflected through justice and deliberation, while the concept of ummah emphasizes the unity of society based on faith. Thus, the thought of Tahir Azhary shows that Islamic nomocracy is not merely a theoretical concept, but also a constitutional model that places law, morality, and public welfare as the main foundations of political life.